The food processor s guide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Setting up and running a small food business. Opportunities in food processing Edited by P J Fellows and B Axtell. CTA, 2001. 298 pp. ISBN 92 9081 246X CTA number 1041. 40 credit points